Análisis de la transformación mecánica y comercialización en el Cantón Valencia Provincia de Los Ríos, año 2018. - Garzón Osorio, Génesis Gabriela (2018)
The present research project was carried out in the Valencia province of Los Ríos, whose general objective is to analyze the different aspects of mechanical transformation and commercialization of wood; for which 10 establishments were identified to which a survey was conducted to their owners in order to identify them by their category, type of establishment, machinery used, volume of products, volume of wood commercialized purchase and sale (m3), origin of wood, main suppliers, quantity of workers, among others. The main machineries used in the establishments are the circular saw, the polisher, planer and moulder, with which they work with the mechanical transformation of the wood. One of the results obtained in this research is that the most commonly used species were determined in the establishments of the canton; such as: Schizolobium parahybum (Vell.) S.F.Blake (pachaco), Maclura tinctoria (L.) D.Don ex Steud (fine moral), Tectona grandis L.f. (teak), Cordia alliodora (Ruiz & Pav.) Oken (laurel), Tabebuia Donnell Smithii (Rose) (white guayacan). The establishments identified were categorized as small, medium and large, in the canton Valencia there are ten establishments of which nine are small (0 m3 to 20 m3) and one medium (21 m3 to 50 m3) being the Quevedo canton with 47% and the parish the Vergel with 32% those that supply with greater amount of wood to all the establishments of the Valencia city. In the one-year extrapolation of the average purchase and sale volume of the establishments, the result was a purchase volume of 376.68 m3 and a sale of 210.96 m3 which, compared to other cantons such as Quevedo, La Maná, Ventanas and Good Faith that have high values of consumption Valencia has small values.